Education in Times of Covid-19. A Look from Different Educational Practices - Aperador, Fredy Esteban; Patino-Cuervo, Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The text presents the results of the research project education in times of coronavirus: discourses and practices of students and teachers, which sought to know the practices used by teachers of an educational institution in the city of Sogamoso, Boyacá, and how these have transformed the reality of students. The study used a qualitative methodological perspective from a critical-social paradigm. Interviews with teachers and students were the main method of data collection. The results of the discourse analysis showed two main aspects: didactic strategies and pedagogical practices, which detail the educational processes experienced by both teachers and students in times of pandemic and how the strategies implemented have an impact on the students’ knowledge.